Citizens' juries in Bogotá: Reflections, achievements, and what comes next - Vollan, Björn (2024)
As we bring our Citizens‘ Juries project in Bogotá to a close, it is time to reflect on the journey, the insights we gained, and the broader implications for deliberative democracy. Over the past months, we have witnessed how deliberation, knowledge-sharing, and collaborative problem-solving can shape perspectives, challenge biases, and produce policy proposals that reflect the priorities of citizens. This blog post offers an overview of the key outcomes, the challenges we encountered, and our reflections on the role of Citizens‘ Juries in participatory governance.